Effects of probiotic supplements on the progression of chronic kidney disease: A meta‐analysis. Issue 11 (30th April 2019) - Tao, Sibei; Tao, Siying; Cheng, Yiming; Liu, Jing; Ma, Liang; Fu, Ping
ABSTRACT: Background: Chronic kidney disease (CKD) is a worldwide public health problem. Although accumulated data suggested that probiotic supplements played roles in CKD, the results remained controversial. Here, we performed a meta‐analysis to assess the effects of probiotic supplements on the CKD progression. Methods: A systematic search was conducted through the PubMed, Embase and Cochrane databases until September 2018. Randomized controlled trials with control receiving placebo, evaluating the effects of probiotic supplements on CKD were included. Results: A total of 10 randomized controlled trials in 8 countries were selected. In the meta‐analysis, urea level was significantly reduced in probiotics‐administrated non‐dialysis patients (mean differences (MD) = −30.01; 95% confidence interval (CI) = [−56.78, −3.25]; P  = 0.03) while no significant change was found in the dialysis patients receiving probiotics (MD = 0.1; 95% CI = [−9.28, 9.48]; P  = 0.98). Probiotic supplements also exhibited no effect on uric acid (MD = −0.43; 95% CI = [−1.19, 0.33]; P  = 0.27), C‐reactive protein (MD = −0.48; 95% CI = [−1.29, 0.33]; P  = 0.24), creatinine (MD = −0.18; 95% CI = [−0.82, 0.47]; P  = 0.59), and estimated glomerular filtration rate (MD = 2.10; 95% CI = [−1.31, 5.52]; P  = 0.23) of CKD patients. Conclusion: Our results highlighted that probiotic supplements exerted a statistically significant effect on urea levels in non‐dialysis CKD population, while no evidence suggested that probiotics possessed meaningful impacts on the reduction of uric acid, C‐reactive protein, creatinine and estimated glomerular filtration rate preservation of CKD population. SUMMARY AT A GLANCE: The effects of probiotic supplements on chronic kidney disease (CKD) progression were evaluated. The authors report a significant effect on reducing urea levels in non‐dialysis CKD population, whereas no significant impact was observed on uric acid, C‐reactive protein, creatinine and estimated glomerular filtration rate.